Liber Uricrisiarum - Daniel, Henry; Harvey, E.Ruth; Tavormina, M. Teresa; Star, Sarah (University of Toronto Press, 2023)
Henry Daniel's Liber Uricrisiarum is the earliest known work of academic medicine written in Middle English, presented here for the first time in a complete edition. Working in the late 1370s, Daniel combined authoritative medicine from written sources with his own personal experience, creating a text that stands out for its linguistic originality, intellectual scope, and wide circulation. Extant in over three dozen manuscript witnesses and two early modern print copies, Liber Uricrisiarum describes medieval humoral theory, anatomy, physiology, disease, medical astronomy, reproductive processes, and more, all within the broader context of uroscopic diagnosis. The introduction situates the text and its author in their medical, intellectual, linguistic, and bibliographic contexts, outlining the uroscopic tradition to which Daniel contributes, and describing the relationships among the many manuscripts containing the Liber Uricrisiarum. This edition presents the Middle English text, with a general glossary, glossary of proper names, and explanatory notes that explain obscure words and phrases and identify Daniel's sources. It also includes the complete set of diagrams contained in the Royal manuscript; appendices providing the Latin and English versions of the prologue and epilogue; an extensive translation from one of Daniel's important sources, Isaac Israeli's De urinis; tables relevant to Daniel's astronomical measurements; and an analysis of the Royal manuscript's dialect. Cumulatively, the edition and apparatus introduce readers to an important yet understudied text, the details of which will have significant impact on studies of medieval medicine and science, intellectual history, and Middle English language and literature.